(untitled) (International Journal of Engineering and Computer Science, 2014)
The growth of image processingused in embedded system has boosted the increase of security in various sectors to a greater extent, we developed a digital watermarking technique for security purpose using discrete wavelet transform (DWT) and Discrete Cosine Transform (DCT).Watermarking technique is highly secure if knowing the exact algorithms for embedding and extracting. Watermark does not help an unauthorized party to detect the presence of the watermark information in it.